Fabrication of reduced graphene oxide-gated AlGaAs/GaAs heterojunction transistor - Azmi, S. N. C. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this report, we discuss possible chemical sensing operation of a graphene-gated AlGaAs/GaAs heterojunction transistor. Band diagram analysis shows the change in transistor conductivity after the graphene work function is altered due to chemical doping by the absorbates. Next, the fabrication process of the device is described and some preliminary results are presented. As for graphene gate, reduced graphene oxide (rGO) was prepared from reduction of graphene oxide solution by ascorbic acid. The reduction process was confirmed by UV-Vis spectroscopy, Raman spectroscopy and current-voltage measurement. Formation of the rGO gate structure in the device could be obtained by a simple procedure involves photolithography and lift-off process.